الأستاذ السعيد ديدي ونشاطه الدعوي والفكري - جبريط, توفيق (University of Eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى التّعريف بالشّيخ والأستاذ السّعيد ديدي – رحمه الله تعالى – وذكر وتدوين مجهوداته التّي بذلها في سبيل الدّعوة إلى الله تعالى، وذكر الاتجاهات التّي نشط فيها, سواء ما عرف بالصّحوة الإسلامية كداعية إلى الله تعالى, أو نشاطه الإسلامي السّياسيّ في أهمّ الأحزاب السّياسية الإسلامية, أو انتقاله إلى الطّريقة التّجانية. كما تعرضّت الدّراسة أهمّ رحلات الأستاذ ديدي داخل وخارجه, إضافة إلى أبرز مؤلفاته. كان الأستاذ السّعيد ديدي شخصية ذات صفات متنوّعة, إذ كان موجّها مرشدا, متواضعا وبسيطا زاهدا وداعية ومصلحا, كما كان فكره على منهج الوسطية والاعتدال والفكرة النقية والقلب الصافي. كرّس حياته خدمة لدينه, وكان حريصا على البحث العلميّ, فقد كان صورة جسّدت لنا حالة الطّالب المجتهد ونموذجا للدّاعية المجدّ." The study aims to introduce Sheikh and professor Al-Saeed Didi - may God Almighty have mercy on him - and mentioned and record his efforts he made for the sake of calling to God Almighty, and mention the directions in which he was active, whether in the direction of the Islamic awakening as a call to God Almighty, or his Islamic political activity, in the most important political parties Islamic, or his transfer to the other direction, which is the intellectual direction under the banner of the Tijani method, and he mentioned his most important trips inside and outside the homeland, and his most important books, and the personality of Al-Saeed Didi was a personality with various qualities, he was directed mentor, modest, simple, ascetic, advocate and reformer, as was his personality on The method of moderation and moderation, the pure idea and the pure heart, the most sincere face of God Almighty, devoted his life in the service of his religion, and he was keen on scientific research, as it was an image that embodied the case of the diligent student and a model for the preacher of glory. "
مذكرة ماستر تخصص دعوة واعلام
Keywords: الأستاذ السّعيد ديدي, الصّحوة الإسلامية, الطّريقة التّجانية.; Al-Saeed Didi, The Islamic Awakening, The Tijani Way